TOTAL DISRUPTION OF PERFORMANCE FOR SOFTWARE PROGRAMMER TEAM SELECTION - Fitria, Fitria; Feta, Neneng Rachmalia (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
The lack of skills of the development team is one factor the failure of software development project team. Interdependency based selection that is considered can increase the chances of team success does not consider skills in the calculation of total disruption of performance. Improvement total disruption of performance formula by adding skill variables can reduce the risk of project failure, in terms of the number of requirements that are delays and bugs/ errors